2017
DOI: 10.1016/j.artd.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Infection burden in total hip and knee arthroplasties: an international registry-based perspective

Abstract: BackgroundInfection remains a leading cause of failure of hip and knee replacements. Infection burden is the ratio of implants revised for infection to the total number of arthroplasties in a specific period, measuring the steady state of infection in a registry. We hypothesized infection burden would be similar among arthroplasty registries.MethodsWe evaluated publicly reported data from 6 arthroplasty registries (Australian Orthopaedic Association National Joint Replacement Registry [AOANJRR], New Zealand Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(130 citation statements)
references
References 23 publications
7
109
2
4
Order By: Relevance
“…We attribute our low overall infection rate to a disci-plined comprehensive TJA protocol focusing on minimizing SSI and PJI. Our selection of the GT dressing for postoperative application did not appear to adversely affect our rates of SSI and PJI when compared to other published series [20]. Our low PJI rate is encouraging in light of our series having 49% B and C grade systemic hosts.…”
Section: Discussionsupporting
confidence: 59%
“…We attribute our low overall infection rate to a disci-plined comprehensive TJA protocol focusing on minimizing SSI and PJI. Our selection of the GT dressing for postoperative application did not appear to adversely affect our rates of SSI and PJI when compared to other published series [20]. Our low PJI rate is encouraging in light of our series having 49% B and C grade systemic hosts.…”
Section: Discussionsupporting
confidence: 59%
“…We found that at tropical sites, patients with positive swabs following surgery were more likely to be younger, male, had undergone knee surgery and have had primary procedures. Age and gender have been well described in the literature as risk factors for infection following orthopaedic surgery, and it is also known from national joint replacement registry data that knee replacements pose a higher risk than for hips [27][28][29][30]. We note that both subtropical sites included in our study are located within the same metropolitan city, while the four tropical sites are regional and remote with substantially lower population densities.…”
Section: Discussionmentioning
confidence: 60%
“…These medications leave transplant patients vulnerable to wound complications and infection, with several previous studies finding increased rates of prosthetic joint infections in solid organ transplant recipients . The reported rate of infection for THA in a general patient population in current literature is around 1% . In this cohort of transplant patients, four of 17 (23.5%) suffered post‐operative infections, with three superficial infections (17.6%), and one deep joint infection (5.9%) requiring surgical management.…”
Section: Discussionmentioning
confidence: 74%